33 The genesis and development of a multidisciplinary atrial fibrillation clinic. (28th September 2016) - Morrissey, E; Pharithi, R; Moore, D; McManamly, C; Burke, C; Collins, R
Abstract : Introduction: Atrial fibrillation (AF) is commonest cardiac arrhythmia. Treatment of AF includes drugs for rate or rhythm control and usually anticoagulation. Direct Oral Anticoagulants (DOACs) are now anticoagulants of choice. Our hospital had no formalised structure for AF management or governance over DOAC treatment. Main stakeholders (cardiology, stroke and pharmacy) agreed development of multi-disciplinary AF clinic. This abstract describes the evolution and set up of such a clinic and the profile of the patients seen (Table 1 ). Methods: A formal plan developed by the stakeholders over 6 week period. European Heart Rhythm Association (EHRA) algorithm adopted as gold standard for monitoring patients on DOACs. Identified pharmacy lead at clinic undertook prescribing course under tutorship of Lead Cardiologist. This facilitated drafting of treatment protocols/data collection forms at clinic. Results: Clinic operates 8 patient slots weekly. There are two patient pathways. Patients return at 1, 4 and 10 months for review and are then discharged back to their GP. To date the clinic has seen over 200 patients over an eleven month time period. Conclusion: This clinic is first multidisciplinary AF clinic of its' kind and we believe it represents an achievable model elsewhere to ensure gold standard treatment of patients with atrial fibrillation. Demand for clinical review of atrial fibrillation is growing so further resourcing will be needed in future as demography changes. An audit on all patient consultations from a Pharmacy and Medical perspective is ongoing to capture the value of this initiative.